PENTINGNYA MENANAMKAN PENDIDIKAN NILAI DI INDONESIA DALAM MEMBENTUK KARAKTER - Iin Nur'aeni; Hidayat Mupid (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2021)
ABSTRACTÂ Globalization requires all aspects to be able to adjust, as well as education which is the spearhead in preparing the nation's generation, to realize the challenge of value education is one way in preparing learners, through value education is expected to form the character of the nation needed as an embodiment in facing the challenges of globalization. Aims to be able to provide understanding to the public in general about the importance of instilling value education in children from an early age, so as to influence character formation as an embodiment of value education in the era of globalization, to achieve this the author focuses on the issues that will be discussed in the environment of value education in shaping character and provide a historical view of the history of value education in Indonesia. In an effort to form character through value education that takes place in educational units implemented through four pillars of activities, namely learning and teaching activities in the classroom, character culture activities in everyday in the school environment; develop an interest in talent in co-curricular or extra-curricular activities, as well as character refraction in his daily life at home and community. Furthermore, value education in an effort to form character continued in the family environment through conscience.Â Keywords: Value Education, Character Education